2011
DOI: 10.1037/a0024057
|View full text |Cite
|
Sign up to set email alerts
|

The subjective experience of social class and upward mobility among African American men in graduate school.

Abstract: We used Consensual Qualitative Research Methodology to analyze responses from 14 African American men (MdnAge = 25 years-old) in graduate school at a predominantly-White university in the Midwestern region of the United Sates regarding how they acquired awareness of their social-class status; how social class was related to their sense of masculinity; how social class was related to race and skin tone; and the role that education and a romantic partner could play in upward mobility. School peers were the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…In a study by Brown, Fukunaga, Umemoto, and Wicker (), any or some combinations of such objective social class indicators do not accurately reflect one's social class identification which is an important factor informing one's sense of belonging (Ostrove & Long, ). On the other hand, an increasing number of quantitative and qualitative studies have reported that subjective social class are related to well‐being, perceptions on higher education, and quality of college experience (Ostrove & Long, ; Sánchez, Liu, Leathers, Goins, & Vilain, ; Singh‐Manoux, Marmot, & Adler, ; Tett, ).…”
Section: Characteristics Of Social Class In Student Affairsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Brown, Fukunaga, Umemoto, and Wicker (), any or some combinations of such objective social class indicators do not accurately reflect one's social class identification which is an important factor informing one's sense of belonging (Ostrove & Long, ). On the other hand, an increasing number of quantitative and qualitative studies have reported that subjective social class are related to well‐being, perceptions on higher education, and quality of college experience (Ostrove & Long, ; Sánchez, Liu, Leathers, Goins, & Vilain, ; Singh‐Manoux, Marmot, & Adler, ; Tett, ).…”
Section: Characteristics Of Social Class In Student Affairsmentioning
confidence: 99%
“…These new environments provide reinforcing, conflicting, or alternative perspectives that dictate one's social class behavior (Liu, ) which make students feel a need to renegotiate their social class identity (Baxter & Britton, ). Moreover, social class is intertwined with students’ other identities (Constantine, ; Jones, ), such as race/ethnicity (Sánchez et al., ), gender (Ostrove, ; Sánchez et al., ; Tett, ), and/or veteran status (Wurster, Rinaldi, Woods, & Liu, ). These identity variables are likely to be related to social privilege and oppression based on students’ social identities.…”
Section: Characteristics Of Social Class In Student Affairsmentioning
confidence: 99%
“…Research has also found that darker-skinned African American men may receive less endorsement to advance their careers, earn significantly lower wages than light-skinned men (Goldsmith, Hamilton, & Darity, 2006) and consider their complexion as a barrier to career success (Sánchez, Liu, Leathers, Goins, & Vilain, 2011). For example, during the 2008 presidential election season, one study tracked skin tone perceptions of then-Senator Barack Obama (an African American Democratic candidate) and found that conservatives and persons that did not vote for Obama estimated his skin tone to be significantly darker than his true complexion (Caruso, Mead, & Balcetis, 2009); in contrast, liberals and persons that voted for Obama estimated that he was significantly more light-skinned than his true complexion.…”
Section: Masculinity and Skin Tone Biases: Complexities With Income Amentioning
confidence: 99%
“…Students from such families often think there is no need to study hard in school because they believe that their needs and future livelihood is largely secure. On the contrary, students from low SES families are often more diligent compared to those from high SES families (Congeret al, 2010;Sánchez et al, 2011;Suyanto, 2001). They are strongly motivated to improve their family income andto self-support further education through scholarships.…”
Section: Introductionmentioning
confidence: 99%